Answer:
10
Step-by-step explanation:
<em>Since it given that:</em>
<em>x = 7 and y = 3</em>
<em>We can substitute x and y:</em>
<em>(7-3) + 2(3)</em>
<em>7 - 3 = 4</em>
<em>4 + 2(3)</em>
<em>2(3) = 6</em>
<em>4 + 6 =10</em>
<em>Thus the answer is 10.</em>
<em />
<em>[RevyBreeze]</em>
<em />
Answer:
<h2>f( - 1) = - 4</h2>
Step-by-step explanation:
f(x) = 3x - 1
To find f(-1) substitute the value of x that's
- 1 into f(x). That's for every x in f(x) replace it with - 1 and solve
That's
f( - 1) = 3(-1) - 1
= - 3 - 1
We have the final answer as
<h3>f(-1) = - 4</h3>
Hope this helps you
Answer:
C: (-8,3) R:5
Step-by-step explanation:
The equation of a circle can be written as:
(x-h)^2+(y-k)^2=r^2
where (h,k) is the center, and r is the radius
We have the equation:
(x+8)^2+(y-3)^2=25
Center:
The center is (-8,3)
(x+8)^2--> (x-h)^2
Therefore the x coordinate of the center is -8
(y-3)^2-->(y-k)^2
Therefore the y coordinate of the center is 3
Radius
r^2=25
Take the square root of both sides
r=5
Answer:
3:5 is less tan 7:10
The ratio 14:20 is greater than the ratio 9:15.
The ratios in Table 1 are less than the ratios in Table 2.
Step-by-step explanation:
3:5 as a fraction is 6/10
7:10 as a fraction is 7/10
3:5 is less
Answer:
Step-by-step explanation:
The answer is A